Safety and efficacy of single dose versus multiple doses of AmBisome for treatment of visceral leishmaniasis in eastern Africa: a randomised trial. - Eltahir A G Khalil; Teklu Weldegebreal; Brima M Younis; Raymond Omollo; Ahmed M Musa; Workagegnehu Hailu; Abuzaid A Abuzaid; Thomas P C Dorlo; Zewdu Hurissa; Sisay Yifru; William Haleke; Peter G Smith; et al. (PLoS Neglected Tropical Diseases)
Background Anti-leishmanial drug regimens that include a single dose AmBisome could be suitable for eastern African patients with symptomatic visceral leishmaniasis (VL) but the appropriate single dose is unknown. Methodology A multi-centre, open-label, non-inferiority, randomized controlled trial with an adaptive design, was conducted to compare the efficacy and safety of a single dose and multiple doses of AmBisome for the treatment of VL in eastern Africa. The primary efficacy endpoint was definitive cure (DC) at 6 months. Symptomatic patients with parasitologically-confirmed, non-severe VL, received a single dose of AmBisome 7.5 mg/kg body weight or multiple doses, 7 times 3 mg/kg on days 1-5, 14, and 21. If interim analyses, evaluated 30 days after the start of treatment following 40 or 80 patients, showed the single dose gave significantly poorer parasite clearance than multiple doses at the 5% significance level, the single dose was increased by 2·5 mg/kg. In a sub-set of patients, parasite clearance was measured by quantitative reverse transcriptase (qRT) PCR. Principal findings The trial was terminated after the third interim analysis because of low efficacy of both regimens. Based on the intention-to-treat population, DC was 85% (95%CI 73-93%), 40% (95%CI 19-64%), and 58% (95%CI 41-73%) in patients treated with multiple doses (n = 63), and single doses of 7·5 (n = 21) or 10 mg/kg (n = 40), respectively. qRT-PCR suggested superior parasite clearance with multiple doses as early as day 3. Safety data accorded with the drug label. Conclusions The tested AmBisome regimens would not be suitable for VL treatment across eastern Africa. An optimal single dose regimen was not identified. Trials registration www.clinicaltrials.govNCT00832208.